Remission, relapse, and risk of major cardiovascular events after metabolic surgery in persons with hypertension: A Swedish nationwide registry-based cohort study - Erik Stenberg (Public Library of Science (PLoS), 2021)
Background Several studies have shown that metabolic surgery is associated with remission of diabetes and hypertension. In terms of diabetes, factors such as duration, insulin use, weight loss, and age have been shown to contribute to the likelihood of remission. Such factors have not been determined for hypertension. The aim of this study was to evaluate factors associated with the remission and relapse of hypertension after metabolic surgery, as well as the risk for major adverse cardiovascular event (MACE) and mortality in patients with and without remission. Methods and findings All adults who underwent metabolic surgery between January 2007 and June 2016 were identified in the nationwide Scandinavian Obesity Surgery Registry (SOReg). Through cross-linkage with the Swedish Prescribed Drug Register, Patient Register, and Statistics Sweden, individual data on prescriptions, inpatient and outpatient diagnoses, and mortality were retrieved. Of the 15,984 patients with pharmacologically treated hypertension, 6,286 (39.3%) were in remission at 2 years. High weight loss and male sex were associated with higher chance of remission, while duration, number of antihypertensive drugs, age, body mass index (BMI), cardiovascular disease, and dyslipidemia were associated with lower chance. After adjustment for age, sex, BMI, comorbidities, and education, the cumulative probabilities of MACEs (2.8% versus 5.7%, adjusted odds ratio (OR) 0.60, 95% confidence interval (CI) 0.47 to 0.77, p < 0.001) and all-cause mortality (4.0% versus 8.0%, adjusted OR 0.71, 95% CI 0.57 to 0.88, p = 0.002) were lower for patients being in remission at 2 years compared with patients not in remission, despite relapse of hypertension in 2,089 patients (cumulative probability 56.3%) during 10-year follow-up. The main limitations of the study were missing information on nonpharmacological treatment for hypertension and the observational study design. Conclusions In this study, we observed an association between high postoperative weight loss and male sex with better chance of remission, while we observed a lower chance of remission depending on disease severity and presence of other metabolic comorbidities. Patients who achieved remission had a halved risk of MACE and death compared with those who did not. The results suggest that in patients with severe obesity and hypertension, metabolic surgery should not be delayed. In a cohort study, Erik Stenberg and colleagues investigate the association between remission, relapse and risk of major cardiovascular events and metabolic surgery in persons with hypertension in Sweden. Author summary Why was this study done? Hypertension, particularly in combination with morbid obesity, is a leading cause of mortality and disability worldwide. There is a growing body of evidence supporting the reduction of major adverse cardiovascular events (MACEs) and mortality among patients with metabolic comorbidities after bariatric surgery. Less is known of the factors associated with remission and relapse of disease as well as the impact on MACEs and morality from reaching remission. The main purpose of this study was to assess which factors that contribute to the remission and relapse of hypertension after metabolic surgery, as well as the risk for MACE and mortality in patients who have achieved remission of hypertension. What did the researchers do and find? In this nationwide observational study, 15,984 patients with hypertension undergoing a primary metabolic procedure were included. Almost 40% of patients with hypertension experienced remission of hypertension 2 years after surgery. While 56% relapsed over 10-year follow-up, those who reached remission experienced lower probability for MACEs and all-cause mortality compared with those who did not reach remission. What do these findings mean? The results of this study suggest that metabolic surgery has the highest success rate for patients early in the course of disease and thus suggests that metabolic surgery should not be delayed for patients with severe obesity and hypertension.